2015
DOI: 10.1002/bkcs.10553
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of the Hydrazones of 2‐((3,5‐Di‐tert‐butyl‐4‐hydroxybenzyl)thio) acetohydrazide and the Study of their Radical Scavenging Activity by the DPPH Assay and the Computational Method

Abstract: The synthesis of antioxidant compounds bearing pharmacologically active groups has become a research interest in the last decade. A series of hydrazones containing a butylated hydroxyl group were synthesized from 2-((3,5-di-tert-butyl-4-hydroxybenzyl)thio)acetohydrazide and various benzaldehyde derivatives, and their radical scavenging activity was explored by 2,2-diphenyl-1-picrylhydrazyl (DPPH) assay and computational calculations. Based on the results, the effects of different substituents on the DPPH IC 50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…However, the color turns into yellow when antioxidant was added into the DPPH solution due to the reduction of divalent nitrogen (N) of DPPH by antioxidant molecule. 22 The radical scavenging activity was expressed by the half maximal inhibitory concentration (IC 50 ), the concentration needed to inhibit 50% of DPPH solution. Thus, the compound which has a lower IC 50 value would shows better antioxidant properties.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the color turns into yellow when antioxidant was added into the DPPH solution due to the reduction of divalent nitrogen (N) of DPPH by antioxidant molecule. 22 The radical scavenging activity was expressed by the half maximal inhibitory concentration (IC 50 ), the concentration needed to inhibit 50% of DPPH solution. Thus, the compound which has a lower IC 50 value would shows better antioxidant properties.…”
Section: Resultsmentioning
confidence: 99%
“…Due to lower electronegativity of sulfur atom, thiol can easily release proton to DPPH radical in comparison of hydroxyl group (Scheme 4). 7,16,22,26 In addition, it was found that the degree of conjugation in thioamides is considerably higher than amides which made it as stronger p-electron attractor. 27 Nevertheless, thiosemicarbazides with thiolated BHT could convert into several radical by donating the proton to reduce DPPH radical.…”
Section: Antioxidant Evaluation By Dpphmentioning
confidence: 99%